Achieving super broadband microwave absorption of aramid honeycomb by filling optimized 3D conductive RGO/melamine foam. (May 2023) - Lu, Junyu; Zhang, Haoruo; Yuan, Mushan; Gao, Yunfei; Liang, Mei; Chen, Yang; Zou, Huawei
Graphical abstract: Abstract: Without a reliable mechanical carrier, it is difficult to apply MA materials in realistic aerospace scenarios. Here, the broadband MA properties of RGO/melamine foam (RGO/MF) composites were prepared and optimized by hydrothermal chemical reduction method. The realization of broadband MA by RGO/MF is mainly achieved through the cooperative enhancement of RGO dispersion by the following two points: (1) three-dimensional (3D) meso -scale dispersion of RGO supplied by MF and (2) 3D microlayer separation of formed RGO provided by hydrothermal chemical reduction. For the first time, we successfully achieve complete filling of the RGO/MF into honeycomb. The RGO/MF honeycomb composites achieved almost 95.25 % EAB in the full frequency ranges from 2 to 18 GHz, where the MA performance of the composites originated from the electric-field loss of the RGO/MFs. Such RGO/MF honeycomb composites shows a promising application prospect and guidance in the field of aerospace stealth.